2020
DOI: 10.21203/rs.3.rs-30436/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Distribution and Determinants of Household Iodized Salt Utilization in Ethiopia: A Spatial and Multilevel Analysis of Ethiopian Demographic and Health Survey

Abstract: Background: Iodine deficiency disorder is a significant public health problem, affecting both developed and developing nations worldwide. It is associated with poor body growth and irreversible mental retardation. However, little is known about the spatial distribution and determinants of household iodized salt utilization in Ethiopia. Therefore, this study aimed to explore the spatial distribution and determinants of iodized salt utilization at national level. Methods : Ethiopian Demographic and Health Survey… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Radio ownership through the years had a positive influence on household iodized salt, pooling the 4 EDHS data, radio ownership decreased the odds of salt iodization. While previous studies 28,29 have found media exposure (which possibly follows the ownership) was effective in rising iodized salt coverage, the pooled effect of radio ownership to decrease the odds is strange. Firstly, ownership is not necessarily media exposure secondly, the type of message could be determinant and thirdly, the influence might be explained by other peculiar characteristics that radio owners exposed and not entered into the analysis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Radio ownership through the years had a positive influence on household iodized salt, pooling the 4 EDHS data, radio ownership decreased the odds of salt iodization. While previous studies 28,29 have found media exposure (which possibly follows the ownership) was effective in rising iodized salt coverage, the pooled effect of radio ownership to decrease the odds is strange. Firstly, ownership is not necessarily media exposure secondly, the type of message could be determinant and thirdly, the influence might be explained by other peculiar characteristics that radio owners exposed and not entered into the analysis.…”
Section: Discussionmentioning
confidence: 85%
“…24,26,27 There have been regional differences in household iodized salt coverage in this study as well as previous studies. 28 From literature including recent analysis from EDHS, these geographical differences might arise from lack of access to messages regarding the use of iodized salt which may encompassed the lack of access to mass media, 29,30 another factor could be market availability of iodized salt. 31 Other factors for regional discrepancies could be knowledge and attitude gaps regarding the deficiencies and associated consequences.…”
Section: Discussionmentioning
confidence: 99%